2022
DOI: 10.3389/fcosc.2021.795365
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Genetic Variation When Far From the Niche Centroid: Prediction for Mangrove Species

Abstract: The niche-centroid hypothesis states that populations that are distributed near the centroid of the species' ecological niche will have higher fitness-related attributes, such as population abundance and genetic diversity than populations near the edges of the niche. Empirical evidence based on abundance and, more recently, genetic diversity data support this hypothesis. However, there are few studies that test this hypothesis in coastal species, such as mangroves. Here, we focused on the black mangrove Avicen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 97 publications
(140 reference statements)
2
9
0
Order By: Relevance
“…This region was amplified using three pairs of primers (trnC-ycf6R, ycf6-psbMR, psbMF-trnD) (Shaw et al, 2005). Sequences obtained were assembled and aligned with the software PhyDE® v0.9971 (Müller et al, 2008).…”
Section: Samples and Dna Sequencingmentioning
confidence: 99%
See 1 more Smart Citation
“…This region was amplified using three pairs of primers (trnC-ycf6R, ycf6-psbMR, psbMF-trnD) (Shaw et al, 2005). Sequences obtained were assembled and aligned with the software PhyDE® v0.9971 (Müller et al, 2008).…”
Section: Samples and Dna Sequencingmentioning
confidence: 99%
“…Several studies have demonstrated a decrease in intraspecific genetic diversity with distance from the niche centroid (e.g. Ochoa‐Zavala et al, 2022), but a potential relationship between niche breadth and phylogeographic patterns across species still requires evaluation.…”
Section: Introductionmentioning
confidence: 99%
“…This study found spatial patterns of changes in suitability, ecological richness, and turnover through the climate change scenarios; however, their magnitude was related to the warming degree. Even though a direct measurement of abundance was not considered in our work, evidence has shown that estimations via ENMs may reflect important fitness parameters of the population, such as abundance and genetic diversity [59][60][61][73][74][75]. In this sense, the results of ENMs can be useful in identifying areas where species abundance may either increase or decrease.…”
Section: Discussionmentioning
confidence: 99%
“…The minimum volume ellipsoid (MVE) algorithm was used as an ENMs tool to represent the species fundamental niche. The election of this algorithm is because empirical and theoretical works assume that fundamental niches have convex shapes, such as ellipsoids [57]; moreover, the distance to the center of an ellipsoid has been shown to be negatively related to fitness attributes, such as population abundance and genetic variation [58][59][60][61]. The MVE is a multivariate estimator that builds ellipsoids spanning a predetermined percentage of observations, predicting a centroid and scattering of the data [62].…”
Section: Algorithm Of the Correlative Ecological Niche Modelsmentioning
confidence: 99%
“…The sea-level fluctuations during glacial-interglacial cycles of the Quaternary might have repeatedly shifted mangroves’ distribution, also influencing genetic diversity ( 2 ). More recently, ongoing climate changes ( 24 , 46 ) and human-induced disturbance ( 47 , 48 ) may have also impacted genetic levels owing to population size reductions in the face of unfavorable niche conditions or by founder effects at the leading edge of new colonizations ( 49 ). Alternative means of dispersal, such as wind and insect-driven pollination ( 21 , 50 ), and human-induced reforestation ( 51 ), can also shape the distribution of genetic diversity in ways (i.e., distance and direction) that may contrast with those from the prevalent oceanographic currents.…”
Section: Discussionmentioning
confidence: 99%